Peningkatan Pengetahuan Kader Asuhan Mandiri tentang Pemanfaatan dan Efek Samping dari Tanaman Obat Keluarga (TOGA) - Sari, Putri Eka; Yulianti, Tanti; Maharani, Ananda (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2024)
Plants have been used to treat various human diseases for thousands of years. Medicinal plants are the main ingredients in tradisional herbal remedies and medicines. With the increasing awarness of healthy lifestyles, family medicinal plants (TOGA) have become an alternative treatment option in the community. The TOGA Self-Care Cadres are at the forefront of efforts to improve public health, especiallu utilization of TOGA. To effectively use TOGA, knowledge is required. This community service activity aims to enhance the knowledge of TOGA Self-Care Cadres regarding the use of TOGA and its potential side effects. The activity was conducted by providing counseling and using pre-test and post-test questionnaires as assesssment intrument for knowledge. The results of the pre-test and post-test were analizyed for normality using the Kolmogorov-Smirnov test, followed by data analysis using the Wilcoxon test. The results showed that in the post-test, 81,25% (13 cadres) had Good knowledge, 18,75% (3 cadre) had Sufficient knowledge, and there were no cadres with Poor knowledge. Statistical tests indicated that the data were not normally distibuted., so the Wilcoxon test was used. Based on the statistical analysis, it can be concluded that the counseling conducted successfully improves the knowledge of TOGA Self-Care Cadres regarding the utilizzation of TOGA and its potential side effects.